Let R 1 = 2 + 2 + 2 − 2 − 2 − . . . be a 5-periodic nested radical, with respective sign pattern is ( + + − − − ) .
Let R 2 , R 3 , R 4 , R 5 be analogous radicals with sign patterns ( − + + − − ) , ( − − + + − ) , ( − − − + + ) , ( + − − − + ) .
Find R 1 − R 5 + R 2 − R 4 + R 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
With infinite series, you have to evaluate it as the limit of the truncated sequence.
Currently, you are assuming that a unique finite limit exists, which needs to be justified.
Log in to reply
I might be wrong but since each R i is less than 2 + 2 + 2 + . . . = 2 , a finite limit exists.
Log in to reply
That only applies if all of the terms are positive. For example, 2 − 4 + 2 … does not exist since we will have 2 − ( 2 + ϵ ) .
Besides, that needs to be stated in the solution in order for the argument to be justified (which is the point in my comment).
Here is a specific example where the "initial iteration setup" leads to the wrong answer.
Especially in cases where we can solve for 2 (or more) finite limiting values, there is uncertainty about which value is the true limit. In certain other cases, there might be finite limiting values, but the sequence either doesn't converge, or tends off to infinity.
1 2 3 4 5 6 7 8 |
|
Is there any other easy method or formula??
Problem Loading...
Note Loading...
Set Loading...
We are going to use the formula 2 cos x = 2 + 2 cos 2 x which is valid for cos x ≥ 0 .
2 cos 1 1 π = 2 + 2 cos 1 1 2 π = 2 + 2 + 2 cos 1 1 4 π = 2 + 2 + 2 + 2 cos 1 1 8 π = = 2 + 2 + 2 − 2 cos 1 1 3 π = 2 + 2 + 2 − 2 + 2 cos 1 1 6 π = 2 + 2 + 2 − 2 − 2 cos 1 1 5 π = = 2 + 2 + 2 − 2 − 2 + 2 cos 1 1 1 0 π = 2 + 2 + 2 − 2 − 2 − 2 cos 1 1 π . It means precisely that R 1 = 2 cos 1 1 π . After that, it is clear from the definitions of R i that R 5 = R 1 2 − 2 = 2 cos 1 1 2 π , R 4 = R 5 2 − 2 = 2 cos 1 1 4 π , R 3 = 2 − R 4 2 = − 2 cos 1 1 8 π = 2 cos 1 1 3 π , R 2 = 2 − R 3 2 = − 2 cos 1 1 6 π = 2 cos 1 1 5 π .
Thus, R 1 − R 5 + R 2 − R 4 + R 3 = 2 cos 1 1 π − 2 cos 1 1 2 π + 2 cos 1 1 3 π − 2 cos 1 1 4 π + 2 cos 1 1 5 π = = 2 cos 1 1 π + 2 cos 1 1 9 π + 2 cos 1 1 3 π + 2 cos 1 1 7 π + 2 cos 1 1 5 π = 2 × 2 1 = 1 .